Idiom-idiom Kematian pada Suku Batak Toba - Tiarnita Maria Siregar; Natasya Euodia Br Ginting; Nazwa Inaya Sani Trisnadi; Sandra Sridevi Hutapea; Susi Eria Agustina Lumbanggaol (Transbahasa, 2024)
This study analyzes 13 types of death idioms in the Batak Toba culture, a sub-ethnic group of the Batak people, to document and understand the uniqueness and complexity of their death customs. A qualitative literature review method was used to collect and analyze data from various relevant written sources. The results show that each death idiom reflects the conditions and social status of the deceased, ranging from the death of children to adults with great-grandchildren. The novelty of this research lies in the detailed documentation and in-depth analysis of each death idiom, providing insights into the values, philosophies, and beliefs of the Batak Toba regarding life and death. This research is significant in the context of cultural preservation and education for future generations. The researchers recommend further studies on the impact of modernization and social changes on the implementation of death customs, as well as the role of technology and media in documenting and disseminating knowledge about these traditions